2021
DOI: 10.1111/jfs.12897
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of aflatoxin M 1 in yogurt of five countries in west Asia region: A systematic review and meta‐analysis

Abstract: Despite the considerable importance of dairy consumption, aflatoxin‐M1 (AFM1) contamination can pose potential health threats for these products. In the present study, we systematically reviewed and conducted a meta‐analysis on the AFM1 contamination in yogurt samples of West Asia region. In the present study, electronic databases including PubMed, Scopus, and web of Science were comprehensively searched for papers published from April 2006 to February 2020 in English language. Of a total of 356 articles found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Regarding the association between DII and inflammation, our findings agreed with recent evidence that DII was associated with elevated CRP levels in non-pregnant populations (90,91) . However, DII scores calculated based on dietary data from both pre-pregnancy and prenatal periods (weighted means), was not associated with early-pregnancy inflammatory biomarkers in an ethnically diverse cohort (92) .…”
Section: Maternal Diet and Prenatal Depression: Mediation Through Pre...supporting
confidence: 91%
“…Regarding the association between DII and inflammation, our findings agreed with recent evidence that DII was associated with elevated CRP levels in non-pregnant populations (90,91) . However, DII scores calculated based on dietary data from both pre-pregnancy and prenatal periods (weighted means), was not associated with early-pregnancy inflammatory biomarkers in an ethnically diverse cohort (92) .…”
Section: Maternal Diet and Prenatal Depression: Mediation Through Pre...supporting
confidence: 91%
“…2019; Mohammadi et al . 2021), most were carried out on milk samples. The results of the present meta‐analysis showed that the total concentration of AFM1 in cheese samples from Qatar (197.74 ng/kg), Turkey (142.02 ng/kg), Iran (124.95 ng/kg), Pakistan (122.56 ng/kg), Kuwait (73.65 ng/kg) and Lebanon (63.98 ng/kg) did not exceed the limit recommended (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These rangelands are vital for animal husbandry in the eastern Anatolia region due to the challenging topography and short growing season (Koç et al, 2021). Additionally, the use of commercial feeds for animal farming is common throughout Türkiye, impacting the utilization of rangelands (Mohammadi et al, 2021).Environmental variables are also under the influence of this situation. One of the most important of these environmental variables is slope.…”
Section: Introductionmentioning
confidence: 99%